Domestic inefficiencies caused by transboundary pollution problems when there is no international coordination of environmental policies - Michael Hoel (University of Oslo, Department of Economics, 2001)
In most models of transboundary pollution, lack of international cooperation does not cause any inefficiency within each country. The paper shows that this result is only valid in the hypothetical case of no international trade. With international trade, we get a domestic inefficiency in addition to the well-known inefficiencies at the international level. More precisely, when there is no cooperation on how to handle transboundary pollution, it is individually rational for each country to choose a policy that gives it a lower welfare than what is possible given the emission levels of all countries.
Keywords: F42; Q20; Q28; Q48; 330; environmental policy; transboundary pollution; carbon leakage; Grenzüberschreitende Umweltbelastung; Internationale Umweltpolitik; Theorie; Koordination